Occupational safety awareness, practice, and their correlation among employees of food and beverage industries of Telangana, India - NG, Sunil Kumar; Pinakapani, Peri; Chellapalli , Thirupathi (International Journal of Occupational Safety and Health, 2025)
Introduction: In all manufacturing sectors, it is very important to ensure workers are informed of potential safety risks because of the implications for public safety, employee welfare, and organizations. This research aims to examine safety hazard awareness in the food and beverage industry (FBI) in Telangana, India, and to investigate the relationship between safety awareness and workplace safety practices.Methods: The study utilized a cross-sectional survey design with data collected from June to August 2023. A random sampling technique was employed, selecting 110 employees from Telangana, India's food and beverage industry. The collected statistical data was analyzed using key statistical indicators, including the Spearman rank correlation coefficient, the Kruskal-Walli’s test, and the Mann–Whitney U test for p-value determination. These analyses were conducted using SPSS.Results: With 90% male participants in the survey and 48.18% from the production department, a significant association between safety awareness and age group and level of education was found with p-values of 0.013 & 0.032 respectively. Similarly, there was a significant association between safety practice, age group, experience level, and job position with p-values of 0.006, 0.0049 & 0.011, respectively. A positive correlation coefficient value of 0.53 represented a noteworthy positive correlation between safety awareness and practice.Conclusion: The findings show that workers have a significant level of awareness regarding safety in the workplace. In addition to that, a noteworthy positive correlation was discovered between safety awareness and safety practices inside the selected food and manufacturing companies of Telangana. Subsequent investigations and studies on safety awareness and hazards will enhance the safety climate and culture across the manufacturing industry.